PENGARUH PROMOTION, LOCATION, FACILITIES, DAN PRICE TERHADAP KEPUASAN CUSTOMER RUMAH KOST SAM SURYA DI KOTA KEDIRI - Muliya, Puja wahyu ning (Universitas Nusantara PGRI Kediri, 2023)
The foundation of this research lies in the contentment with the existing promotions, the strategic assessment of the location, the perceived adequacy of facilities, and the relatively affordable pricing at the Sam Surya boarding house in Kediri. The primary objective of this study was to comprehensively assess how promotion, location, facilities, and pricing individually and collectively impact customer satisfaction at the Sam Surya boarding house in Kediri. Employing a quantitative methodology and a survey-based approach, this research aimed to gather insights. Through a non-probability sampling technique, a total of 40 respondents were included. The analysis was conducted using the SPSS version 23 software, utilizing multiple linear regression. The results of the study revealed a favorable connection between the variables of promotion, location, facilities, and pricing, and customer satisfaction at the Sam Surya boarding house in Kediri. This suggests the importance of the boarding house focusing on enhancing their promotion strategies, optimizing their location, ensuring satisfactory facilities, and maintaining competitive pricing. These actions are expected to enhance the overall quality of the Sam Surya boarding house in the future.